The Use and Concurrent Use of Side Effect Controlling Medications Among Women on Aromatase Inhibitors - Farkas, Amy H. (J Womens Health (Larchmt), 2021)
Background: Women on aromatase inhibitors (AIs) as part of their breast cancer treatment often experience difficult to control side effects. Although there are several medications to manage the side effects of AI therapy, many of them are associated with their own risk, particularly sedation. The objective of this study was to describe the prescribing practices for side effect managing (SE) medications among women with breast cancer on AI therapy and to assess for combinations of medications that may present a clinical risk to patients. Methods: Retrospective data analysis using Surveillance, Epidemiology and End Results (SEER)-Medicare data of all women aged 66–90 years with stage I–III hormone positive breast cancer diagnosed between 2008 and 2014 who initiated AI therapy within 12 months of their diagnosis. We determined the percentage of patients prescribed an SE medication in the 12 months prior and in the 24 months after the initiation of AI therapy. We calculated the number of prescriptions and the number of days of overlapping (i.e., >1 SE) prescriptions, and examined predictors of overlapping prescriptions. Results: The use of SE medications was pervasive and increased after initiation of AI therapy. The most commonly prescribed medications were opiates (55.1%), selective serotonin reuptake inhibitors (22.6%), benzodiazepines (18.4%), tramadol (17.7%) and gabapentin (14.6%). In total 15.5% of patients had overlapping prescriptions; among those, 36.2% had three overlapping prescriptions. Prior use was the strongest predictor of overlapping prescriptions with an odds ratio of 7.9 (95% confidence interval: 7.17–8.77). Conclusion: Among women on AI therapy, the use of SE medications is common and many have overlapping prescriptions raising concern for potential harm from polypharmacy.